The role of microRNAs in the involvement of vascular smooth muscle cells in the development of atherosclerosis. (16th July 2019) - Li, Linqing; Li, Yongjun; Tang, Chengchun
Abstract: MicroRNAs (miRNAs) are a class of nonprotein‐encoding RNAs of ~22 nucleotides in length that bind to or complement each other with a target gene messenger RNA (mRNA) to promote mRNA degradation or inhibit translation of the target mRNA. The protein required [such as Toll‐like receptor (TLR) proteins] is controlled at an optimal level. By affecting protein translation, miRNAs have become powerful regulators of biological processes, including development, differentiation, cell proliferation, and apoptosis. MiRNAs are involved in the regulation of proliferation, migration, and apoptosis of vascular smooth muscle cells (VSMCs), thereby affecting the formation of atherosclerosis (AS). In recent years, the role and mechanism of miRNAs involved in AS development in VSMCs have been studied extensively. In the current study, the results and progress in miRNA research are reviewed.